A framework for environmental policy evaluation in the South African mining sector - Rainer Thiele (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
This paper presents a Computable General Equilibrium (CGE) model for the analysis of environmental policies towards mining activities, and shows for the case of South Africa how it can be implemented numerically. The CGE model belongs to the class of static, trade-focussed models along the lines suggested by Dervis et al. (1982). A distinctive feature of the model is that it allows for substitution possibilities between primary factors and intermediate inputs such as energy and mineral resources. In the South African data base, two different types of households (black and other households) are distinguished in order to trace the distributional consequences of policy reforms which are of high priority given the income inequalities prevailing in South Africa.
Keywords: D58; Q32; 330; computable general equilibrium model; mining; South Africa; environmental policy; Umweltpolitik; Bergbau; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; Faktorsubstitution; Einkommensverteilung; Social Accounting Matrix; Südafrika